2019
DOI: 10.1002/adfm.201902652
|View full text |Cite
|
Sign up to set email alerts
|

Metal Species–Encapsulated Mesoporous Silica Nanoparticles: Current Advancements and Latest Breakthroughs

Abstract: Despite their advantageous morphological attributes and attractive physicochemical properties, mesoporous silica nanoparticles (MSNs) are merely supported as carriers or vectors for a reason. Incorporating various metal species in the confined nanospaces of MSNs (M-MSNs) significantly enriches their mesoporous architecture and diverse functionalities, bringing exciting potentials to this burgeoning field of research. These incorporated guest species offer enormous benefits to the MSN hosts concerning the reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
79
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 124 publications
(88 citation statements)
references
References 308 publications
0
79
0
Order By: Relevance
“…Impregnation of the outermost wall of the MSNs by active metal compounds (Al and Cu) is a recent advancement in the eld of MSN-based drug delivery systems to reduce the deleterious effect of nanoparticles on biological systems. 103 This study shed light on the bridge between various hydrothermal resistances of MSNs such as HMS, MSU, MCM, and SBA families of silica and surface roughness. Here, HMS (hollow mesoporous silica) and MSU (Michigan State University) silica (made from Tergitol and Tween surfactants) with the lowest surface roughness show higher hydrothermal and mechanical resistance.…”
Section: Particle Morphology and Surface Modicationmentioning
confidence: 93%
“…Impregnation of the outermost wall of the MSNs by active metal compounds (Al and Cu) is a recent advancement in the eld of MSN-based drug delivery systems to reduce the deleterious effect of nanoparticles on biological systems. 103 This study shed light on the bridge between various hydrothermal resistances of MSNs such as HMS, MSU, MCM, and SBA families of silica and surface roughness. Here, HMS (hollow mesoporous silica) and MSU (Michigan State University) silica (made from Tergitol and Tween surfactants) with the lowest surface roughness show higher hydrothermal and mechanical resistance.…”
Section: Particle Morphology and Surface Modicationmentioning
confidence: 93%
“…Poor colloidal and thermal stabilities can result in drawbacks with long-term storage and nanosystems administration. In this sense, MSNs present robust silica framework and exceptional electronic architecture easily optimized, making them amazing nanoarchitectures with interesting structural stability for biomedical applications (174). Additionally, authors reported that the association of MSNs with metals such as iron, Pt, Al and others, can improve the nanoplatforms thermal and physical stabilities considering a critical ratio of metal to silica content (174).…”
Section: Clinical Translation Challenges and Future Outlookmentioning
confidence: 99%
“…Various types of mesoporous carriers like MCM-41, MCM-48, SBA-15, SBA-16, and SBA-12 with unique morphology, pore size, and structure are known [ 2 , 3 ]. The surface of the MPS can be modified and tailored by modification with metal nanoparticles, using different approaches and preparing advanced functional materials [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%